EVALUATING THE CONTRIBUTION OF PHYSICAL PARAMETERS ON THE SAFETY OF UNSIGNALIZED INTERSECTIONS - A. AHMED; A. F. M. SADULLAH; A. S. YAHYA (Journal of Engineering Science and Technology, 2015)
Safety of any particular Road way facility cannot be attributed to set of parameters specific to a certain domain. Unsignalized intersections are no exceptions, thus, making them an important area of study. This paper presents the results of the analysis of four parameters, namely road width, traffic control, lane marking and landuse; and their sub-class on the safety of unsignalized intersections. The raw accident data was obtained from MIROS (Malaysian Institute of Road Safety Research). It was then reduced for descriptive analysis. Hypothesis testing was performed to assess the significance of all parameters and severity analysis was done to accomplish micro scale examination of each sub-class. The results show that landuse and lane marking are statistically significant. They are important variables to predict accidents whereas traffic control and road width are not significant. Intersections located in city with single line lane marking having no control and major road width greater than 9 meters were found to have the highest severity indices.